A Comparative Behaviour Study of Three Deer Species under Farm Management Systems in Malaysia - Ahmad, Zaiton (1997)

(untitled)
The objectives of this study were: 1) to compare the grazing behaviour of three deer species viz. Cervus timorensis, Dama dama and Axis axis farmed under similar conditions - on the Right-Of-Way (ROW) of Petronas Gas Sdn. Bhd. (PGSB) - a strip of land measuring 40 meters wide carrying the gas pipeline; 2) to determine the stocking rate for each deer species; 3) to determine the most suitable species to be farmed in Malaysia in general and specifically on ROW; 4) to determine a suitable management system relating to the animal behaviour, pasture use and stocking rate. Data collection for this study were conducted from July 1993 until August 1995 and were carried out at PGSB, Parit Baru and Ceremin Kiri Deer Farms and Dewan Bandaraya Kuala Lumpur (DBKL) Deer Park. All three deer species showed similar grazing behaviour represented by a bi-modal pattern with two major peaks. They were observed to graze predominantly at night (A. axis - 30.8%, C. timorensis - 41 .7%, D. dama - 1 6.7%) indicating their nocturnal nature. D. dama, being a temperate species also exhibited modification of grazing behaviour due to high temperature conditions (mean daily maximum temperature - 34.5 C) on ROW. Overt heat stress was exhibited by D. dama. Deviation from natural patterns due to supplementation was also noted in all three deer species. Experiments on intake of different sub-groups (matured males and females, and juveniles) of C. timorensis revealed that juveniles showed the highest intake (1.34% of live body weight), followed by matured males (1.19%) and the least by matured females (1.10%). However, these rates were very much lower than those obtained from other studies that did not include supplementation. Stocking rate was found to be highest when using Panicum maximum with 26.73 heads per hectare for A. axis, 19.09 heads for C. timorensis, and 24.30 heads for D. dama. The least number was recorded for native pasture. C. timorensis was concluded to be the most suitable species to be farmed commercially in Malaysia followed by D. dama and the least was A. axis. The management system which was found to be suitable on ROW would be that which provides ample shade preferably vegetative in nature, especially when D. dama was being used. Improved pasture using Panicum maximum would ensure optimum production since stocking rate was found to be highest when compared with other grass types. The possibility to habituate D. damn was seen at DBKL Deer Park, while at the other three farms 'adoption' phenomenon was observed in C. timorensis. These factors could be exploited to optimise production.